The Effect of Current Ratio, Debt to Equity Ratio, Return on Assets to Dividend Payout Ratio in Food and Beverage Companies Listed on The Indonesia Stock Exchange - Diah Ayu Puspitasari; Rahmat Agus Santoso (INNOVATION RESEARCH JOURNAL, 2023)
ABSTRACT The purpose of this study was conducted to determine the effect of the Current Ratio, Debt to Equity, Return On Assets on the Dividend Payout Ratio in Food and Beverage companies listed on the Indonesia Stock Exchange in 2017-2020. This type of research is associative research. The data analysis technique used in this research is quantitative. Data collection techniques in this study using documentation techniques. In this study the authors calculated the liquidity ratio, namely the Current Ratio, calculated the solvency ratio, namely the Debt to Equity Ratio, calculated the profitability ratio, namely Return on Assets and also the market value ratio, namely the Dividend Payout Ratio. Sampling using purposive sampling method using certain criteria. The study sample consisted of 120 companies. The results of this study indicate that Current Ratio has a positive effect on the Dividend Payout Ratio, Debt to Equity Ratio has a positive effect on the Dividend Payout Ratio and Return on Assets has a negative effect on the Dividend Payout Ratio in Food and Beverage companies listed on the Stock Exchange Indonesia in 2017-2020.